Strategies to improve writing skills: karen - Lainez Rivera, Shirley Antonieta (2024)
There is a case of study about Karen. Who has problems when creating short text messages in English, about topics related to her environment, especially when she needs to write some specific imaginary stories, the student is motivated to learn the language, she needs to use basic structures in order to make coherent texts that allow her to communicate her writing effectively, and in this case she shows frustration when she can't find the appropriate vocabulary to express her thoughts. The use of the dictionary is difficult for her to manage and she doesn't know how to organize the words in order to make a sentence and at the same time to associate it with an imaginary situation. There is not any specific didactic strategy that generates the student's concern for the development of this skill, demonstrating her low performance in the writing of the English as a language in a general form. So, her level of English is poor in writing.